Wave Drift Force and Moment in Deep and Shallow Water - Heinrich Söding (Journal of Marine Science and Engineering)
To attain a low Energy Efficiency Design Index (EEDI), large ships possibly lack the necessary propulsion power to avoid stranding in case of strong adverse wind and wave conditions. To estimate this danger, here, the longitudinal and transverse drift force and the yaw drift moment caused by regular waves of arbitrary frequency and direction are computed using a 3-dimensional Rankine panel method. In many cases, drift forces are larger in shallow than in deep water. Therefore, the theory for computing drift force and moment is extended to shallow water. As published results for shallow water are lacking, the method is verified only for deep water by comparisons with results of model experiments and CFD computations for three ships. For one of them, the dependence of non-dimensional coefficients of longitudinal and transverse drift force and of the drift yaw moment on wave frequency, wave angle, water depth and ship speed is shown. The source files of the programs used for these computations may be obtained from the author if an adequate fee is donated to the Medecins Sans Frontieres or to the author.